Human Resource Management practices that translate into sustainable competitive advantage - Ewa Bułat (The Central European Review of Economics and Management (CEREM), 2019)
Aim: The aim of the paper is to delve into the Human Resource Management (HRM) practices which undoubtedly translate into enhanced business performance. The article combines the theoretical study of HRM with its application to professional practice in order to provide a comprehensive analysis of the reasons and ways of implementing good HRM processes.~Design/Research methods: A desk case study approach has been adopted to conduct a descriptive-comparative analysis of two prosperous corporations operating in distinct sectors.~Conclusions/findings: It is suggested that the analysed companies have been consistently outperforming their competitors due to their HRM practices which can be linked back to the seminal motivation theories and concepts relating HRM to performance. It seems that especially the application of AMO framework and Path-Goal Theory to workplace scenarios can yield good results, regardless of the industry.~Originality/value of the article: This study not only provides an insight into the HRM practices which appear to contribute most to improved productivity, but it also attempts to shed some light on the how and why of their application. So far, much of the empirical research has confirmed a significant statistical connection between HRM practices and business success, but relatively little attention has been paid to understanding the exact mechanisms through which conceptual HRM practices can be implemented. An attempt to address this gap is the value added of the paper.~Implications: The findings may prompt the upper echelons of power in companies to fit the appropriate HR practices into their business strategies to achieve the organisational objectives.
Keywords: J24; M12; J28; J32; M53; L21; 330; human capital; talent management; motivation theories; non-cash incentives; training and development; sustainable competitive advantage